First Report of Crown and Root Rot Caused by Fusarium solani on Photinia × fraseri Dress in China - Zhou, Jing (Plant disease, 2022)
Photinia × fraseri Dress was introduced to China at the end of the 20th century. It is a kind of colorful ornamental tree species with great ornamental value. From 2020 to 2021, a disease was found in Railway Gymnasium, Xuanwu district of Nanjing which approximately 40% P. × fraseri showed symptoms of blight with discoloration and dieback of crown and root . Symptomatic root tissues collected from three 2-year-old plants were rinsed with water, cut into 2-mm pieces which were surface-sterilized in 70 % ethanol for 60 s, and plated onto Potato Dextrose Agar (PDA), and incubated in the dark at 26 °C for 3 days. Mycelium emerged from 75 % of the samples. Two representative isolates (SG31, SG32) were obtained and deposited in China's Forestry Culture Collection Center. The colony growed in a circular shape, and the early aerial hyphae were white. Later a floccose, white, colony which was dull yellow on the underside was observed . The two isolates had identical morphological features. The macroconidia were sickle-shaped with two to three septa, 22.8 - 43.7 µm × 4.1 - 5.8 µm in size (n=50). The microconidia were numerous, oval, fusiform, renal, or oblong, with zero or one septum, 10.96 - 14.63 µm × 3.89 - 5.76 µm in size (n=50). The hyphae begin to germinate from one or both ends of the spore . Thus, the two isolates were identified as Fusarium solani. For molecular identification, the DNA of the two isolates was extracted. The internal transcribed spacer (ITS) region, β-tubulin (TUB2), and actin gene (ACT) region were amplified using the primer pairs ITS5 / ITS4, T1 / T2 , and ACT-512F / ACT-783R), respectively. The sequences were deposited in GenBank under accession numbers ON329814, ON366356, and ON366358 for SG31 and ON329813, ON366357, and ON366359 for SG32. The ITS, TUB2, and ACT sequences of isolate SG31 were 99.83% (574 / 575 nt), 99.81% (517 / 518 nt), and 100% (248 / 248 nt) identical to those of SF_450 (MT529726.1), CH64 (KU938961.1), and Co.Karbala-IQ1 (MW080737.1), respectively (The comparison results of SG32 were shown in Appendix.). Based on morphological and molecular analysis, the two isolates were identified as F. solani. The pathogenicity of SG31 and SG32 were tested on potted 1-yr-old (30-cm tall) P. × fraseri. Nine plants were dug up to expose root balls, which were wounded before inoculations with a sterile needle, and then inoculated with conidial suspension (106 conidia / mL). Controls were treated with ddH2O. Three seedlings/isolate were used for each treatment. All plants were repotted using the original sterilized potting mix and pots. After inoculation, the plants were covered with plastic bags, and sterilized H2O was sprayed into the bags twice per day to maintain humidity and kept in a greenhouse at the day/night temperatures at 25 ± 2 / 16 ± 2 ℃. Within 30 days, all the inoculated plants showed lesions similar to those observed in the field, whereas controls were asymptomatic. The isolates were reisolated from the lesions (whereas not from controls) and sequenced as F. solani. Globally, this is the first report of F. solani causing crown blight and root rot of P. × fraseri. Additional surveys are being conducted for mapping the distribution of F. solani in Jiangsu Province of China